Progression of atrophy of the corpus callosum with deterioration of cerebral cortical oxygen metabolism after carotid artery occlusion: a follow up study with MRI and PET. Issue 4 (October 1995) - Yamauchi, H; Pagani, M; Fukuyama, H; Ouchi, Y; Nagahama, Y; Matsuzaki, S; Kimura, J; Yonekura, Y; Konishi, J
Abstract : In cerebrovascular disease, progression of brain atrophy may reflect an increase in ischaemic changes. The purpose of this study was to determine whether atrophy of the corpus callosum progresses in association with a deterioration in cerebral cortical oxygen metabolism after occlusion of the carotid artery. Magnetic resonance imaging and PET were used to serially evaluate six patients with occlusion of the unilateral internal carotid artery at intervals ranging from 12 to 50 months. One patient had no symptoms, one had a transient ischaemic attack, and four had a minor stroke. All patients had presented at most only subcortical lesions at the first evaluation. During follow up, no patient showed extension of subcortical lesions or recurrent stroke. The initial total callosal area:skull area ratio for the patients was significantly less than that for 14 age matched normal control subjects. The yearly decrease of callosal size in the patients, which differed significantly from zero and exceeded that in the controls, was significantly correlated with the deterioration in mean cerebral cortical oxygen metabolism. Three of the four patients who showed significant progression of callosal atrophy presented deterioration in haemodynamic states as well. It is concluded that in some patients atrophy of the corpus callosum progresses after occlusion of the carotid artery even in the absence of any overt episode of stroke, and that this atrophy is associated with deterioration in cerebral cortical oxygen metabolism. An increase in cerebral morphological changes with deterioration in cerebral metabolism related to ischaemia may occur after occlusion of the carotid artery, even in the absence of symptoms.